PERANAN KEPALA SEKOLAH DALAM MANAJEMEN BERBASIS SEKOLAH (MBS) - Hidayanthi, Rahma; Andini, Selfi; Fitri, Hasanatul; Gistituasti, Nurhizrah; Rusdinal, Rusdinal (Cerdas Proklamator, 2022)
School-Based Management (SBM) is the authority given to schools to manage or regulate everything that is needed for autonomy (independently) including school policies. This authority is exercised by the principal as the head of the school. However, current school principals still need to improve managerial competence so that they understand their role in schools. The purpose of this study was to find out how the principal in implementing SBM. This study uses qualitative research because the research carried out aims to describe aspects that are the context in research related to the role of school principals in the implementation of SBM. Effective principal leadership in SBM can be seen based on the criteria, namely (1) Being able to empower the competencies possessed by teachers. (2) Able to complete tasks on time. (3) Able to communicate and involve the community for the interests and goals of schools and education. (4) Able to carry out the principles of leadership well. (5) able to implement together with the management team (6) Able to make schools productive in improving students' abilities.